2009
DOI: 10.1074/jbc.m109.013375
|View full text |Cite
|
Sign up to set email alerts
|

The Tether Connecting Cytosolic (N Terminus) and Membrane (C Terminus) Domains of Yeast V-ATPase Subunit a (Vph1) Is Required for Assembly of V0 Subunit d

Abstract: V-ATPases are molecular motors that reversibly disassemble in vivo. Anchored in the membrane is subunit a. Subunit a has a movable N terminus that switches positions during disassembly and reassembly. Deletions were made at residues securing the N terminus of subunit a (yeast isoform Vph1) to its membranebound C-terminal domain in order to understand the role of this conserved region for V-ATPase function. Shrinking of the tether made cells pH-sensitive (vma phenotype) because assembly of V 0 subunit d was har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The "beam" that extends between the fingers is shown to cradle the H subunit and contact the d subunit, although this latter interaction is likely transient or manifest only when V 1 and V 0 are dissociated. These interactions have been demonstrated elsewhere (25,59), but the precise assembly is speculative. Both ends of the beam, which traverses ϳ120°around the rotor axis, are thought to support one each of three EG heterodimer peripheral stalks, and one end contacts the C subunit, which supports the third EG heterodimer at its distal end (see also C).…”
Section: Discussionmentioning
confidence: 99%
“…The "beam" that extends between the fingers is shown to cradle the H subunit and contact the d subunit, although this latter interaction is likely transient or manifest only when V 1 and V 0 are dissociated. These interactions have been demonstrated elsewhere (25,59), but the precise assembly is speculative. Both ends of the beam, which traverses ϳ120°around the rotor axis, are thought to support one each of three EG heterodimer peripheral stalks, and one end contacts the C subunit, which supports the third EG heterodimer at its distal end (see also C).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot-Vacuolar membrane protein was separated by SDS-PAGE in 8% polyacrylamide gels and transferred to a nitrocellulose membrane, and V-ATPase subunits a, A, and B were visualized with the monoclonal antibodies 10D7, 8B1, and 13D11 as described previously (35).…”
Section: Other Methodsmentioning
confidence: 99%
“…Yeast vph1⌬stv1⌬ does not express endogenous subunit a, because the gene VPH1 and its functional homolog, STV1, are deleted (34). Previously, we showed that biosynthetic assembly of tether-less V 1 V 0 (vph1-362-407⌬) complexes is complete when cells modestly overexpress V 0 subunit d (Vma6p) and that the assembled vph1-362-407⌬ V 1 V 0 fully retains ATP hydrolytic activity (35). Thus, we simultaneously co-transformed the vph1⌬stv1⌬ cells with VPH1-362-407⌬ and subunit d (VMA6), each of them expressed from a CEN plasmid (pRS316) under control of their natural promoters as described previously (35).…”
Section: Tether Connecting the Cytosolic Domain Of Subunit A (Vph1p) mentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinking, two-hybrid screening, coimmunoprecipitation, and electron microscopy showed that the a-subunit isoforms directly interact with A-, E-, H-, C-, and G-subunits of the V 1 sector [9][10][11][12][13] as well as with c-and d-subunits of the V o sector. 2,[14][15][16] Recently, it has also been shown that the V-ATPase a-subunit directly assembles with proteins that are not part of the V-ATPase complex including: (i) aldolase B, 17,18 (ii) phosphofrucktokinase-1, 19,20 (iii) calmodulin, 21 and (iv) t-SNARES syntaxin and SNAP-25. 22 However, the mechanisms and molecular details of interactions with these proteins remain poorly understood, mainly due to the lack of a high-resolution structure of the a-subunit and the absence of studies designed for mapping interaction sites on both the a-subunit and its associated proteins.…”
Section: Introductionmentioning
confidence: 99%